Failed States, Governance and Nation-Building: The Case of Afghanistan - Mills, Greg (2016)
Rebuilding failed states - from Afghanistan to Zimbabwe - is conventionally taken to fundamentally be an exercise in extending governance. In most cases, this occurs from the capital out; in others, it is argued more effective to create several centres of governance - or 'ink spots' - which will radiate outwards in the rural and urban areas.